PENGARUH KECUKUPAN MODAL, PEMBIAYAAN, EFISIENSI BIAYA, RESIKO PEMBIAYAAN, DAN KUALITAS AKTIVA PRODUKTIF TERHADAP RETURN ON ASSETPADA BANK UMUM SYARIâAH PERIODE 2012-2016 - DwiPolahWicaksonowati, 13.05.52.0249; Puspitasari, Elen (Students Journal of Accounting and Banking, 2018)
This research was aimed and analyze at examining the influence of Capital Adequacy ratio, Financing to Deposit Ratio, Operating Expenses per Operating Income, Non Performing Financing, and Allowance for Earning Assets to profitability in Islamic Commercial Banks.Â Research conducted a quantitave study with the entire population of Islamic Banks registered in Financial Fervices Autority (OJK) on 2012-2016, byÂ usingÂ purposiveÂ samplingÂ method. TypesÂ ofÂ dataÂ usedÂ areÂ secondaryÂ dataÂ obtainedÂ fromÂ publishedÂ financial statementÂ andÂ downloadedÂ throughÂ theÂ officialÂ websiteÂ ofÂ Islamic Commercial Banks. The method of analysis used is Multiple Regression with a significance level of 5%. From the results of the analysis show thatÂ Capital Adequacy Ratio , Operating Expenses per Operating Income, Allowance for Earning Assets hasÂ significant influence to profitability, while Financing to Deposit Ratio,Â and Non Performing Financing have not significant influence to profitability. Keyword : Capital Adequacy Ratio, Financing to Deposit Ratio, Operating Expenses per Operating Income, Non Performing Financing, Allowance for Earning Assets,Â Â Return On Assets